Elaboração e avaliação da confiabilidade de um instrumento para medição da qualidade de vida relacionada à saúde de idosos independentes Development and reliability evaluation of an instrument to measure health-related quality of life in independent elderly - Maria José Barbosa de Lima; Margareth Crisóstomo Portela (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Este trabalho apresenta um instrumento, o QUASI - Perfil de Qualidade de Vida Relacionada à Saúde de Idosos Independentes, para a medição da qualidade de vida relacionada à saúde de idosos que freqüentam programas ambulatoriais, a partir da adaptação de quatro instrumentos amplamente validados: Short-Form Health Survey, Duke-UNC Health Profile, Sickness Impact Profile e Nottingham Health Profile. Além disso, avalia a confiabilidade, considerando a sua utilização por dois entrevistadores, em intervalo de 15 dias. O instrumento contempla cinco dimensões: Percepção de Saúde, Sintomas, Função Física, Função Psicológica e Função Social e envolve 45 itens. A avaliação da confiabilidade foi realizada a partir das entrevistas de 142 idosos, inscritos em programas ambulatoriais no Município do Rio de Janeiro, Brasil, com base na apreciação da estatística kappa, ajustada por prevalência, para cada um dos 45 itens incluídos, e na correlação dos escores geral e por dimensão. Na avaliação da confiabilidade, 39 dos 45 itens apresentaram kappa superior a 0,60. This study presents an instrument, the health-related quality of life (HRQOL) profile for independent elderly, to measure the health-related quality of life of the functionally independent elderly assisted in the outpatient setting, based on the adaptation of four validated scales: Short-Form Health Survey (SF-36), Duke-UNC Health Profile (DUHP), Sickness Impact Profile (SIP), and Nottingham Health Profile (NHP). The study also evaluates the instrument's reliability based on its use by two different observers with a 15-day interval. The instrument includes five dimensions (health perception, symptoms, physical function, psychological function, and social function) and 45 items. Reliability evaluation of the QUASI instrument was based on interviews with 142 elderly outpatients in the city of Rio de Janeiro, Brazil. Prevalence-adjusted kappa statistic was used to assess all 45 items. Correlation was also calculated between overall scores and scores on individual dimensions. In the reliability evaluation, 39 of the 45 items showed prevalence-adjusted kappa greater than 0.60.